Icodextrin reduces adhesion formation following gynecological surgery in rabbits - Behnaz Khani1; Nahid Bahrami; Ferdous Mehrabian; Hormoz Naderi Naeni (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
AbstractBackground: Adhesion is a common complication of gynecology surgery so different barrier agents and solutions have been used during these operations to separate and protect tissues from adhesion after surgery. Adept is one of these solutions that have been postulated to reduce the chance of adhesion following gynecolgy surgery.Objective: To evaluate the effect of 4% icodextrin in reducing adhesion formation in comparing with sterile water and human amniotic fluid in rabbits.Materials and Methods: In this prospective experimental study 30 white Newzealand female rabbits were selected and randomized in to three treatment groups. The rabbits were anesthetized and an abdominal incison was made, uterine horns were abrated with gauze until bleeding occurred. Before closing the abdomen, the traumatized area was irrigated either by 30cc of sterile water, 30cc of 4% Adept or 30cc of human amniotic fluid. The solutions were labeled only as solutions A (steriel water), B (icodextrin), or C (human amniotic fluid). On the seventh day after surgery, second laparotomy was performed to determine and compare adhesion formation in rabbits.Results: There was significant difference between mean score of adhesions in 4% icodextrin group (2.1±0.70) in comparison to sterile water group (10.4±0.60) and amniotic fluid group (8.7±0.84). But the difference between mean score of adhesions in amniotic fluid group in comparison to sterile water group was not significant (8.7±0.84) versus (10.4±0.60).Conclusion: The use of 4% icodextrin solution was more effective than human amniotic fluid and sterile water in reducing adhesion formation in a gynecological surgery model in rabbits